2019
DOI: 10.1039/c8ra09129c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel rambutan-like graphene@aluminum composite spheres and non-destructive terahertz characterization

Abstract: Synthesis of novel rambutan-like graphene@aluminum composite spheres by MPCVD, and the evaluation of shell thickness by a non-destructive terahertz technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Figure 3 b shows the high-resolution C1s spectra of HA and PHA. The binding energy peaks centered at 283.04, 283.82, 286.00, and 287.50 eV for HA and at 283.01, 283.76, 286.00, and 287.48 eV for PHA are assignable to C–C, C–H, C–O, and C=O, respectively (see Supplementary Table S3 online) 27 30 . Compared with HA, the relative amount of C–C in PHA decreased by 18.5%, while C–H increased by 29.6%, which indicated that the relative proportion of protonated C was higher than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 b shows the high-resolution C1s spectra of HA and PHA. The binding energy peaks centered at 283.04, 283.82, 286.00, and 287.50 eV for HA and at 283.01, 283.76, 286.00, and 287.48 eV for PHA are assignable to C–C, C–H, C–O, and C=O, respectively (see Supplementary Table S3 online) 27 30 . Compared with HA, the relative amount of C–C in PHA decreased by 18.5%, while C–H increased by 29.6%, which indicated that the relative proportion of protonated C was higher than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…FDTD Simulations: The frequency-dependent scattering cross-sections of THz near-field Pt probes with different shaft lengths, i.e., 60, 80, 100, 120, and 140 µm, were investigated using the FDTD method (Lumerical Solutions, Vancouver, British Columbia, Canada). [27,32,33] Since Pt has high electrical conductivity in the THz range, the Pt probes were regard as perfect electric conductors. In the simulation, a plane wave with a frequency region of 0.5-3.0 THz was illuminated on the Pt conical rod probe with a curvature radius of 60 nm and cone opening angle of 40°.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting time‐domain THz near‐field signals ( Figure a) show that the graphene or Au surface present the highest peak values (≈4 times or ≈6 times higher than that of Si or mica, respectively), indicating their high THz reflection efficiency. The corresponding frequency‐domain spectra derived from fast Fourier transformation (FFT) [ 27 ] (Figure 2b) also shows that the graphene or Au surface exhibit much higher dynamic range (≈42 dB) compared to that of Si (30 dB) or mica surface (20 dB). In the frequency‐domain spectra, quite a few peaks appear in the region between 0.5 and 1.6 THz (signals at frequencies >1.6 THz are noisy thus can be ignored).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were carried out under a well‐controlled environment with a temperature of 21.0 ± 0.4°C and a humidity of 50 ± 2%. The obtained time‐domain data were transformed into frequency‐domain data by the fast Fourier transform algorithm, 28 and the electric‐field amplitude was extracted at different frequencies. THz images were constructed from the amplitude data of each pixel at different frequencies.…”
Section: Methodsmentioning
confidence: 99%